Long term follow up of patients after allogeneic stem cell transplantation and transfusion of HSV-TK transduced T-cells - Weissinger, Eva M.; Borchers, Sylvia; Silvani, Anna; Provasi, Elena; Radrizzani, Marina; Beckmann, Irene K.; Benati, Claudia; Schmidtke, Joerg; Kuehnau, Wolfgang; Schweier, Patrick; Luther, Susanne; Fernandez-Munoz, Ivonne; et al. (Frontiers in Pharmacology, 2015)
Allogeneic stem cell transplantation (allo-HSCT) is one of the curative treatments for hematologic malignancies, but is hampered by severe complications, such as acute or chronic graft-versus-host-disease (aGvHD; cGvHD) and infections. CD34-selcetion of stem cells reduces the risk of aGvHD, but also leads to increased infectious complications and relapse. Thus, we studied the efficacy, safety and feasibility of transfer of gene modified donor T-cells shortly after allo-HSCT in two clinical trials between 2002 and 2007 and here we compare the results to unmodified donor leukocyte transfusion (DLI). The aim of these trials was to provide patients with the protection of T-cells after T-cell-depleted allo-HSCT in the matched or mismatched donor setting with an option to delete transduced T-cells, if severe aGvHD occurred within the trial period. Donor-T-cells were transduced with the replication-deficient retrovirus SFCMM-3, expressing HSV-Tk and the truncated LNGFR for selection of transduced cells. Transduced cells were transfused either after day +60 (matched donors) or on day +42 (haploidentical donors).Nine patients were included in the first trial (MHH; 2002 until 2007) 2 were included in TK007 (2005-2009) and 6 serve as a control group for outcome after haploidentical transplantation without HSV-TK-transduced DLI. Three patients developed acute GvHD, two had grade I of the skin, one had aGvHD on day +131 (post-HSCT; +89 post-HSV-Tk DLI) grade II, which was successfully controlled by ganciclovir (GCV). Donor chimerism was stabilized after transfusion of the transduced cells in all patients treated. Functionality of HSV-Tk gene expressing T-cells was shown by loss of bcr-abl gene expression as well as by control of cytomegalovirus-reactivation. To date, 6patients have relapsed and died, 2 after a second HSCT without T-cell depletion or administration of unmodified T-cells. Eleven patients (7 post-HSV-Tk DLI) are alive and well to date.